Factors Associated With Stunting Incidents In Toddlers Aged 24-59 Months In Cimahi City In 2022 - Lia, Kamila; SD, Rahmizani; Ririn, Heriawanti (MIDWIFERY JOURNAL, 2023)
Background: Chronic hunger, recurrent illnesses, and psychological stimulation all contribute to stunting, a condition of failure to thrive in children under five. There were 167 children with stunting who had their data documented at the Citeureup Health Center. Due to the increasing nutritional requirements for children this age, toddlers between 24 and 59 months have a propensity to be undernourished, which makes kids more susceptible to illness.Finding out what contributes to the prevalence of stunting in children between the ages of 24 and 59 in the Citeureup sub-district is our main goal.Methods: A case-control study approach was used for this study. Simple random sampling is used in the sampling method. The sample for this study consisted of 118 toddlers, 59 of whom had stunting and 59 of whom did not. Chi-Square was utilized for bivariate data analysis, and logistic regression was employed for multivariate data.Results: The nutritional status of the mother during pregnancy (p=0.001; OR 4.194), history of LBW (p=0.001; OR 8.195), exclusive breastfeeding (p=0.000; OR 15.750), and age at first giving complementary foods (p = 0.001; OR 4.052) were factors that significantly correlated with the incidence of stunting. Exclusive breastfeeding accounted for the majority of the variance (exp(B)=3.157; OR 23.503).Conclusion: There is a relationship between the nutritional status of mothers during pregnancy, history of low birth weight, exclusive breastfeeding and age at first giving complementary foods to the incidence of stunting. The most dominant factor is exclusive breastfeeding.Suggestion : It is recommended that midwives work together with cadres to further increase mothers' understanding of the importance of monitoring toddler growth and development at posyandu so that they can detect toddlers who experience failure to thrive earlier and monitor toddlers who experience growth faltering by maximizing KMS. Keywords: Nutritional Status of Mother during Pregnancy, History of LBW, Exclusive Breastfeeding, Age at First Giving MPASI, Stunting ABSTRAK Latar Belakang: Stunting adalah kondisi gagal tumbuh pada anak usia balita akibat kekurangan gizi kronis, infeksi berulang dan stimulasi psikososial. Data balita stunting yang tecatat di Puskesmas Citeureup sebanyak 167 balita. Balita usia 24-59 bulan memiliki kecenderungan menderita status gizi kurang disebabkan asupan gizi yang diperlukan untuk anak seusia ini meningkat, yang menyebabkan anak lebih mudah sakit.Tujuan: Mengetahui faktor-faktor yang berhubungan dengan kejadian stunting pada balita usia 24-59 di kelurahan Citeureup.Metode: Penelitian ini merupakan penelitian  dengan desain case control. Teknik pengambilan sampel menggunakan simple random sampling. Sampel penelitian ini berjumlah 118 balita yaitu 59 kasus stunting dan 59 kontrol. Analisis data menggunakan Chi-Square untuk bivariat dan regresi logistik untuk multivariat.Hasil: Faktor yang memiliki hubungan secara signifikan dengan kejadian stunting adalah status gizi ibu saat hamil (p= 0,001; OR 4,194) riwayat BBLR (p= 0,001; OR 8,195), pemberian ASI eksklusif (p= 0,000 ; OR 15,750)dan usia pertama pemberian MPASI (p= 0,001; OR 4,052). Variabel yang paling dominan yaitu pemberian ASI eksklusif (exp(B)=3,157 ; OR 23,503).Simpulan: Terdapat hubungan antara status gizi ibu saat hamil, riwayat BBLR, pemberian ASI eksklusif dan usia pertama pemberian MPASI dengan kejadian stunting. Faktor yang paling dominan adalah pemberian ASI eksklusif.Saran: Bidan bekerjasama dengan kader untuk dapat lebih meningkatkan pemahaman ibu tentang pentingnya pemantauan tumbuh kembang balita di posyandu agar dapat lebih awal mendeteksi balita yang mengalami gagal tumbuh dan pemantauan balita yang mengalami growth faltering dengan memaksimalkan KMS.  Kata Kunci : Status Gizi Ibu saat Hamil, Riwayat BBLR, ASI Eksklusif, Usia Pertama Pemberian MPASI, Stunting